Dinamika Kepemimpinan Modern - Danang Nugroho; Vira Citra Lestari; Warningsih Ade Rahmawati; Shifa Nurfitria H R; Nadya Putri Shabira; Yovi Rahmat Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the dynamic era of current business and organizations, leadership role has become the key to achieving success and sustainability. The author analyzes the main characteristics of transformational leadership and how this approach can be applied to effectively achieve organizational goals through literature review. The conceptual analysis results identify the positive impact of transformational leadership on organizational culture, employee motivation, and significant achievement of results.